Modulation of genotoxicity and endocrine disruptive effects of malathion by dietary honeybee pollen and propolis in Nile tilapia (Oreochromis niloticus) - Mohamed M.M. Kandiel; Amel M. El-Asely; Hasnaa A. Radwan; Amany A. Abbass (Journal of Advanced Research, 2014)
The present study aimed at verifying the usefulness of dietary 2.5% bee-pollen (BP) or propolis (PROP) to overcome the genotoxic and endocrine disruptive effects of malathion polluted water in Oreochromis niloticus (O. niloticus). The acute toxicity test was conducted in O. niloticus in various concentrations (0–8 ppm); mortality rate was assessed daily for 96 h. The 96 h-LC50 was 5 ppm and therefore 1/5 of the median lethal concentration (1 ppm) was used for chronic toxicity assessment. In experiment (1), fish (n = 8/group) were kept on a diet (BP/PROP or without additive (control)) and exposed daily to malathion in water at concentration of 5 ppm for 96 h “acute toxicity experiment”. Protective efficiency against the malathion was verified through chromosomal aberrations (CA), micronucleus (MN) and DNA-fragmentation assessment. Survival rate in control, BP and PROP groups was 37.5%, 50.0% and 100.0%, respectively. Fish in BP and PROP groups showed a significant (P < 0.05) reduction in the frequency of CA (57.14% and 40.66%), MN (53.13% and 40.63%) and DNA-fragmentation (53.08% and 30.00%). In experiment (2), fish (10 males and 5 females/group) were kept on a diet with/without BP for 21 days before malathion-exposure in water at concentration of 0 ppm (control) or 1 ppm (Exposed) for further 10 days “chronic toxicity experiment”. BP significantly (P < 0.05) reduced CA (86.33%), MN (82.22%) and DNA-fragmentation (93.11%), prolonged the sperm motility when exposed to 0.01 ppm of pollutant in vitro and increased the estradiol level in females comparing to control. In conclusion, BP can be used as a feed additive for fish prone to be raised in integrated fish farms or cage culture due to its potency to chemo-protect against genotoxicity and sperm-teratogenicity persuaded by malathion-exposure.